Kajian Implementasi Early Warning Score System (EWSS) Sebagai Dasar Penyusunan Plan of Action di Salah Satu Rumah Sakit Swasta Tipe B - Bantono, Agus Rustam; Susilaningsih, F. Sri; Murtiningsih, Murtiningsih; Budiman, Budiman; Setiawati, Setiawati; Inayah, Iin (Journal of Telenursing (JOTING), 2025)
Background: Early Warning Score System (EWSS) is a system to assess changes in patient conditions in order to respond quickly when deterioration occurs and has been implemented since 2018. At the beginning of implementation, regulations have been prepared, education has been carried out supported by the use of the Hospital Management Information System (SIMRS). The results of the investigation, Early Warning Score (EWS) is carried out routinely and handover is not optimal. Doctor interviews, stated that EWS was reported only with a red grading. The achievement of EWS monitoring in 235 medical records, 85% were not carried out and EWS follow-up was yellow grading 0%. Improvement efforts have been made through coordination meetings, but have not been evaluated.Objective: The study aims to analyze the implementation of EWSS and compile improvement efforts.Method: The research method is wide, participatory and responsive action research model Kurt Lewin with stages of planning, action and fact finding. The study is limited to the planning stage. The sample uses total sampling of EWS assessment in medical records based on the number of beds and the number of minimum actions for EWS assessment in the first 24 hours of inpatient admission. Data collection was carried out by reviewing medical records followed by Focus Group Discussion (FGD) to strengthen the data. The medical record review was analyzed using Quantitative analysis (descriptive statistics) while the FGD used qualitative analysis followed by the preparation of the Plan of Action (POA).Results: The findings of the medical record review were grouped based on the EWS assessment process flow in inpatient care, while the FGD was grouped according to its theme.Optimal nurse understanding was not related to the implementation of EWS where 57.5% of patients' EWS assessments, 7.9% were not assessed for 24 hours and the EWS assessment time span since being admitted to inpatient care was 11 hours 22 minutes. The data is related to the results of the FGD related to factors that influence its implementation, namely vital signs regulation, supervision, critical thinking, and SIMRS is not yet user friendly. The problems that emerged and were compiled in the POA were TTV measurement regulations, EWS assessments were not optimal, EWSS supervision was still weak and SIMRS was not yet user friendly. Conclusion: The results of the review of medical records of new patients were mostly admitted in the afternoon shift (49.8%), EWS assessment of new patients 57.5%, since the first 24 hours of new patients being hospitalized 7.9% were not given an EWS assessment, EWS grading yellow which was re-assessed (2x/shift) 10.8%), the range of EWS assessments since being admitted to hospital was 11 hours 22 minutes. Four themes of results: EWS as early detection, technical understanding of EWS assessment, EWSW implementation in inpatients and factors influencing EWS implementation. The problems that emerged and the POA drafted for TTV measurement regulations were not yet in sync with EWS assessment regulations, EWSS supervision was still weak, EWS assessment was not optimal, SIMRS was not user friendly.Suggestion: Research recommendations are to improve critical thinking, increase medical team involvement, improve supervision, review EWS regulations and implementation of POA that has been drafted. Keywords: EWS, EWSS, EWS implementation study